Níveis de fitase em dietas com ajustes nutricionais para frangos de corte - Henrique Barbosa de Freitas (2021)
This study was carried out with the objective of evaluating the supplementation of increasing doses and superdosing of phytase in broiler diets formulated with reduced levels of available phosphorus, calcium and sodium on the metabolism of nutrients and energy in the diet. A total of 900 male broilers were distributed in a completely randomized design with six treatments and five replications of 30 birds each. Three nutritional matrices were considered: Matrix A: 0.165% calcium (Ca), 0.150% available phosphorus (avP) and 0.035% sodium (Na); Matrix B: 0.215% Ca, 0.195% avP and 0.045% Na and Matrix C: 0.245% Ca, 0.225% avP and 0.053% Na. The treatments were: Without Phytase (formulated to meet nutritional requirements and without enzyme); Phytase 500+MT A; Phytase 1,000+MT A; Phytase 1,500+MT A; Phytase 1,000+MT B and Phytase 1,500+MT C. The use of the Phytase 1,500+MT C diet provided improved metabolization of nutrients, such as: dry matter, crude protein, phosphorus and ether extract, in addition to an increase in diet energy when phytase was supplemented at 1,500 FTU/kg, however when the enzyme was supplemented at 1,000 FTU/kg associated with matrix A and B, the observed results showed improvement or maintenance of the evaluated parameters. Broilers that received the 1,500+MT C diet showed greater metabolizability of the nutrients evaluated in addition to increased energy compared to the diet without phytase, translating into greater use of nutrients. Increasing doses of phytase associated with reduced Pd, Ca and Na improve the digestibility of nutrients and energy for broilers at 21 and 42 days of age. Phytase supplementation at the level of 1,500 FTU/kg associated with a nutritional matrix of 0.225% avP, 0.245% Ca and 0.053% Na, proved to be effective, making it possible to consider more robust nutritional matrix in addition to phytase superdosing in the period from 1 to 42 days.